Seroprevalence of Five Important Viral Diseases in Commercial Chickens in Grenada, West Indies - Sharma , Ravindra N.; Tiwari, Keshaw P.; Chikweto, Alfred; Thomas, Derek; DeAllie, Claude; Stratton, Graeme; Bhaiyat, Muhammad I. (International Journal of Poultry Science, 2014)
This study was conducted to estimate the seroprevalence of New Castle disease (ND), Infectious bursal disease (IBD), Chicken infectious anemia (CIA), Avian Pneumovirus (APV) and Avian influenza (AI) in commercial chickens in Grenada, West Indies. In total, 226 and 233 sera were collected, respectively from layer (6 to 18 months age) and broiler (6 to 7 weeks of age) chickens in six regions (parishes) of Grenada and were tested using commercial ELIZA kits. The overall seroprevalence of ND, IBD, CIA, APV and AI was 47.7% (95% CI; 41.2-54.2%), 34.7% (95% CI, 28.4-40.9%), 92.9% (95% CI; 89.5-96.2%), 61.9 (95% CI, 55.6-68.2%) and 0%, respectively for layers and 48.25 (95% CI, 41.85-54.6%), 40.35 (95% CI,34.0-46.6%), 58.3% (95% CI, 52.0-64.2%), 31.7% (95% CI.25.7-37.7%) and 0%, respectively for broilers. The presence of antibodies for more than one disease agent in the same chicken indicates that several pathogens are circulating within the same premises. This survey shows that major poultry diseases are threatening the productivity of commercial chickens in Grenada. This is the first report on disease surveillance in commercial chickens in Grenada.